Cyclin-like proteins tip regenerative balance in the liver to favour cancer formation. (2nd October 2019) - Fifield, Bre-Anne; Talia, John; Stoyanovich, Carlee; Elliott, Mitchell J; Bakht, Martin K; Basilious, Amy; Samsoondar, Joshua P; Curtis, Madison; Stringer, Keith F; Porter, Lisa A
Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths worldwide. A variety of factors can contribute to the onset of this disease, including viral infection, obesity, alcohol abuse and non-alcoholic fatty liver disease (NAFLD). These stressors predominantly introduce chronic inflammation leading to liver cirrhosis and finally the onset of HCC; however, approximately 20% of HCC cases arise in the absence of cirrhosis via a poorly defined mechanism. The atypical cyclin-like protein Spy1 is capable of overriding cell cycle checkpoints, promoting proliferation and has been implicated in HCC. We hypothesize that Spy1 promotes sustained proliferation making the liver more susceptible to accumulation of deleterious mutations, leading to the development of non-cirrhotic HCC. We report for the first time that elevation of Spy1 within the liver of a transgenic mouse model leads to enhanced spontaneous liver tumourigenesis. We show that the abundance of Spy1 enhanced fat deposition within the liver and decreased the inflammatory response. Interestingly, Spy1 transgenic mice have a significant reduction in fibrosis and sustained rates of hepatocyte proliferation, and endogenous levels of Spy1 are downregulated during the normal fibrotic response. Our results provide support that abnormal regulation of Spy1 protein drives liver tumorigenesis in the absence of elevated fibrosis and, hence, may represent a potential mechanism behind non-cirrhotic HCC. This work may implicate Spy1 as a prognostic indicator and/or potential target in the treatment of diseases of the liver, such as HCC. The cyclin-like protein Spy1 enhances lipid deposition and reduces fibrosis in the liver. Spy1 also promotes increased hepatocyte proliferation and onset of non-cirrhotic hepatocellular carcinoma (HCC). Thus, Spy1 may be used as a potential target in the treatment of HCC.